Subjectivity Construction of Chinese Rural Women’s political Participation: Perspective of Rural Governance Modernization - Xuqing Zhou; Lai, Yew Meng (Secholian Publication (Kuala Lumpur, Malaysia), 2023)
In China’s urban-rural dual development pattern and the process of industrialization and urbanization, a large number of young and middle-aged men in rural areas have moved to cities and towns to work. Both permanent population and agricultural labor force in rural areas have presented the characteristics of feminization, and rural women have become the main force of rural development. However, rural women are still in a subordinate position in rural political participation, and it is difficult for them to play their subjective role. In 2019, China issued an official document to promote the modernization of rural governance which reflects China’s feature of coordinated rural governance by multiple subjects. Therefore, this paper assumes that the rural multi-subject governance system proposed by China provides a good opportunity to construct the subjectivity of Chinese rural women’s political participation. By the methods of gender analysis, comparative analysis and literature analysis, this paper explores methods to construct the subjectivity of rural women’s political participation under the background of the modernization of rural governance from the construction of rural women’s subjectivity by themselves and the participation of all parties of the state and society in order to improve the level of Chinese rural women’s political participation, narrow the gap between rural gender political participation, promote the process of gender equality in political participation, promote the political democratization of China’s rural areas, and achieve their own comprehensive development.